Intrahepatic biliary cystadenoma with ciliary metaplasia: Report of a rare morphological variant - Gaurav Khanna; Pragya Sharma; K S Madhusudhan; Adarsh Barwad; Piyush Ranjan; Biplab Mishra; Prasenjit Das (Wolters Kluwer Medknow Publications, 2017)
Histological diagnosis of biliary cystadenoma is based on the type of epithelial cells lining the cyst and radiological features. The cyst-lining cells are not usually ciliated. We herein report a very rare example of an intrahepatic biliary cystadenoma with ciliated epithelial lining, which had taken us away from this diagnosis toward an intrahepatic foregut duplication cyst. Radiologically, also the lesion was deceptive, and a possibility of hydatid cyst was considered. However, immunohistochemical workup finally led us to this diagnosis. This report would document this rare morphological variant, which may pose diagnostic difficulty.